1981
DOI: 10.1177/070674378102600412
|View full text |Cite
|
Sign up to set email alerts
|

Depression Associated with Cimetidine

Abstract: Over the past three years we have seen twelve patients who have become depressed while taking cimetidine. Clinically the depression is similar to that seen in a Primary Affective Disorder. Two representative cases are presented. It is suggested that cimetidine has precipitated a depressive reaction is vulnerable patients. Tricyclic antidepressants are effective in relieving the depression. It is postulated that cimetidine, by blocking H2 receptors in the CNS, produces an imbalance between H1 and H2. This imbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In contrast, several cases of depression induced by cimetidine were reported (Johnson and Bailey 1979;Crowder and Pate 1980;Billings et al 1981;Pierce 1983). Billings et al (1981) suggested an imbalance between H 1 R and H 2 R signaling by the inhibition of the latter receptor, but disregards that several antidepressants are also moderately potent H 2 R antagonists. Antell et al (1989), however, negated any association of depression and cimetidine.…”
Section: Structure-activity Relationships For Antidepressants and Antmentioning
confidence: 91%
“…In contrast, several cases of depression induced by cimetidine were reported (Johnson and Bailey 1979;Crowder and Pate 1980;Billings et al 1981;Pierce 1983). Billings et al (1981) suggested an imbalance between H 1 R and H 2 R signaling by the inhibition of the latter receptor, but disregards that several antidepressants are also moderately potent H 2 R antagonists. Antell et al (1989), however, negated any association of depression and cimetidine.…”
Section: Structure-activity Relationships For Antidepressants and Antmentioning
confidence: 91%
“…It must be emphasized that the experience with cimetidine revealed that, where mental confusion occurred, the patients were generally elderly and had coexistent renal and/or hepatic impairment. The cases of depression, however, which have been linked to cimetidine tended to occur in younger and healthier patients (Johnson and Bailey, 1979;Crowder and Pate, 1980;Billings et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Cimetidine is a known cause of mental confusion, especially in the elderly and in those with renal and/or hepatic impairment (Russell and Lopez, 1980). Furthermore, cimetidine has been associated with depression (Johnson and Bailey, 1979;Crowder and Pate, 1980;Billings, Tang and Rakoff, 1981), even in physically healthy younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the H 1 R antagonist terfenadine showed antidepressant-like activity in the olfactory bulbectomized model of depression [Song et al, 1996]. The H 2 R antagonist cimetidine showed depression-like activity in vulnerable patients and was suggested to be caused by an imbalance between H 1 R and H 2 R [Billings et al, 1981]. Indeed, this effect of cimetidine was also seen in animal models of depression and could be antagonized by co-administration of the H 1 R antagonist chlorpheniramine [O'Neill and Gertner, 1986].…”
Section: Role Of Histamine In Depressionmentioning
confidence: 97%